2018
DOI: 10.1186/s12985-018-1052-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of B-cell epitopes within envelope protein of tembusu virus

Abstract: BackgroundTembusu virus is a newly emerging flavivirus that caused egg-drop syndrome in ducks in China. TMUV envelope protein is a major structural protein locates at the surface of tembusu virus particle. During tembusu virus infection, envelope protein plays a pivotal role in induction of neutralizing antibody. However, B cell epitopes within envelope protein have not been well studied.MethodA series of 13 peptides derived from E protein of tembusu virus were synthesized and screened by Dot blot with tembusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Tembusu virus (TMUV) is a newly emerging flavivirus that causes rapid egg drop and neurological symptoms in ducks. Potential in silico predicted B-cell epitopes of the E protein of TMUV fused with glutathione S-transferases tag have been successfully expressed in Escherichia coli [ 89 ]. The findings suggested that two of the four predicted B-cell epitopes could elicit the generation of neutralizing antibodies in ducks and provide protection when challenged with TMUV [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tembusu virus (TMUV) is a newly emerging flavivirus that causes rapid egg drop and neurological symptoms in ducks. Potential in silico predicted B-cell epitopes of the E protein of TMUV fused with glutathione S-transferases tag have been successfully expressed in Escherichia coli [ 89 ]. The findings suggested that two of the four predicted B-cell epitopes could elicit the generation of neutralizing antibodies in ducks and provide protection when challenged with TMUV [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential in silico predicted B-cell epitopes of the E protein of TMUV fused with glutathione S-transferases tag have been successfully expressed in Escherichia coli [ 89 ]. The findings suggested that two of the four predicted B-cell epitopes could elicit the generation of neutralizing antibodies in ducks and provide protection when challenged with TMUV [ 89 ]. A chimeric recombinant antigen comprising of predicted CD4+ and CD8+ T cell-specific epitopes derived from Leishmania infantum was successfully expressed in E .…”
Section: Discussionmentioning
confidence: 99%
“…Duck anti-TMUV serum was prepared and stored in our laboratory. The neutralizing antibody titre of the antiserum was assessed by the plaque reduction neutralization test as previously described (Zhao et al, 2018a). Duck peripheral blood lymphocytes were isolated using a duck peripheral blood lymphocyte isolation kit (Haoyang, Tianjin, China) according to the manufacturer's protocol.…”
Section: Ade Inhibition Assaysmentioning
confidence: 99%
“…Current strategies for epitope identification depend upon detection of epitopes within an individual full-length protein, a low-throughput approach that requires prior knowledge of the antigenic protein, its sequence, and its conformational structure. Technologies to screen for epitopes at the whole proteome level have been developed (e.g., proteomic microarrays, phage and yeast display); however, these technologies require extensive use of synthetic biology and other time-consuming methodologies (e.g., library construction, peptide/protein array preparation, heterologous protein expression) (3,(5)(6)(7)(8)(9)(10)(11). Another major disadvantage of display technologies and use of non-native expression systems is that these methods do not reliably replicate the native properties of the antigenic proteins, including their post-translational modifications, which can lead to inaccurate identification of epitopes.…”
Section: Introductionmentioning
confidence: 99%